PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS LECTORA INSPIRE UNTUK MENINGKATKAN HASIL BELAJAR IPAS MATERI KEBERAGAMAN BUDAYA PADA PESERTA DIDIK KELAS IV SDN JATINGALEH 01 KOTA SEMARANG - Dewi, Nadya Puspita; Farid Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the lack of technology utilization in the learning process, which resulted in low learning outcomes among students. The development of Lectora-based learning media is one solution to this problem. This study aims to identify and test the developed media based on its feasibility, practicality, and effectiveness. The research method used is Research and Development (RnD) with the ADDIE development model. The subjects of this study are fourth-grade students of SDN Jatingaleh 01, with a population of 27 students, 3 students as a small-scale pilot test, and 24 students as a large-scale test. The feasibility test results, based on evaluations by media and content experts, yielded scores of 92.2% and 94%, meeting the criteria for “highly feasible.” The practicality test results, derived from teacher and student response surveys, yielded scores of 93% and 96%, meeting the criteria for “highly practical.” The results of the media effectiveness test were based on pre-test and post-test scores conducted in two stages, small-scale and large-scale, with scores of 0.81 and 0.74, respectively, which fall under the high criteria. The overall findings suggest that the interactive learning media utilizing Lectora Inspire is appropriate, applicable, and effective for implementation in the learning process of fourth-grade students at SDN Jatingaleh 01 in Semarang City.